EFFECT OF CALCINATION TEMPERATURE ON F-DOPED LiFePO4 CATHODE MATERIAL ON FORMATION OF OLIVINE PHASE - Ramadhani, Ahmad Ilham; Noerochim, Lukman; Susanti, Diah; Sari, Eli Novita (Indonesian Physical Review, 2021)
Olivine single phase of LiFePO4 was successfully synthesized by solid-state reaction (SSR) method through the formation of Fe2P2O7 from precursors of Li2CO3, F2O3, NH4H2PO4, and LiF as materials doping. Variations at temperatures of calcination 670 0C, 700 0C and 750 0C with doped 0.1F. TGA-DSC test results show that the LFP sample undergoes decomposition in the temperature range 0-600 0C. The olivine phase formed at temperatures of more than 650 0C and the oxidation process on the LiFePO4/C sample was completed, and the sample mass was constant. The olivine phase formed was determined by comparing the 2ðœƒ value obtained through characterization with the ICDD LFP (01-081-1173), and accordingly with experiment. The increase of the temperature results from a dominant LFP phase with a larger grain size. The effect of increasing the calcination temperature at 0.1F has resulted in an enlargement of the particle size.